The SnAC Domain of SWI/SNF Is a Histone Anchor Required for Remodeling - Sen, Payel (American Society for Microbiology, 2013)
The SWI/SNF chromatin remodeling complex changes the positions where nucleosomes are bound to DNA, exchanges out histone dimers, and disassembles nucleosomes. All of these activities depend on ATP hydrolysis by the catalytic subunit Snf2, containing a DNA-dependent ATPase domain. Here we examine the role of another domain in Snf2 called SnAC (Snf2 ATP coupling) that was shown previously to regulate the ATPase activity of SWI/SNF. We have found that SnAC has another function besides regulation of ATPase activity that is even more critical for nucleosome remodeling by SWI/SNF. We have found that deletion of the SnAC domain strongly uncouples ATP hydrolysis from nucleosome movement. Deletion of SnAC does not adversely affect the rate, processivity, or pulling force of SWI/SNF to translocate along free DNA in an ATP-dependent manner. The uncoupling of ATP hydrolysis from nucleosome movement is shown to be due to loss of SnAC binding to the histone surface of nucleosomes. While the SnAC domain targets both the ATPase domain and histones, the SnAC domain as a histone anchor plays a more critical role in remodeling because it is required to convert DNA translocation into nucleosome movement.